Quantity And Quality Of Production The Asri Art Bone Waste Carving - Ida Ayu Nyoman Yuliastuti; Putu Kepramareni; Anak Agung Putu Wiwik Sugiantari; I Ketut Sudipta Giri (Journal of the Community Development in Asia (JCDA), 2019)
Asri art bone waste carving is one of the carving cow and buffalo bone waste which is an icon of Tampaksiring Village. Some problems faced by Asri are not having a place to store raw materials, the quantity of production is still relatively low, and product quality control is still lacking. To overcome these problems, the solutions provided are making raw material storage, providing production equipment, as well as making and assisting in the implementation of Standard Operating Procedures for production. The results of this activity are the quality of Asri's raw materials to be better maintained, the quantity of Asri's production has increased, and the quality of the products produced can be controlled.